2022
DOI: 10.1007/s00431-022-04458-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase of Kawasaki disease: a review of national guideline recommendations

Abstract: Key aspects of the medical management of Kawasaki disease (KD) are not yet supported by a high evidence level, thus making room for individual recommendations. We performed a structured comparison of existing international KD guidelines to analyze potential differences in the implementation of evidence-based KD recommendations regarding diagnosis and therapy. To identify country-specific guidelines, we took a multilateral approach including a comprehensive PubMed literature, online research, and directly conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
14
0
5
Order By: Relevance
“…e duration of treatment is 6-8 weeks in KD patients without CAA. However, in patients with CAA, antiplatelet therapy is continued until resolution of the lesions or indefinitely in case of persistence [12][13][14]. Nakada's retrospective analysis showed that children receiving IVIG and aspirin at the same time can reduce the incidence of coronary artery disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…e duration of treatment is 6-8 weeks in KD patients without CAA. However, in patients with CAA, antiplatelet therapy is continued until resolution of the lesions or indefinitely in case of persistence [12][13][14]. Nakada's retrospective analysis showed that children receiving IVIG and aspirin at the same time can reduce the incidence of coronary artery disease [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, these clinical presentations are not often present at the same time or in the typical order of appearance [ 57 ]. Furthermore, only 70% to 80% of patients completely fulfill the KD criteria, and this percentage decreases in younger children [ 58 ]. Therefore, doctors who only suspect KD must perform repeat histories and careful examinations to timeously diagnose KD in FC.…”
Section: Discussionmentioning
confidence: 99%
“…A high dose of intravenous immunoglobulin (IVIG, 2mg/kg) and aspirin are the standard treatment for KD and was shown to be effective in decreasing aneurysm formation from 20–25% to 3–5% [ 1 , 2 ].The definition of incomplete KD and IVIG-resistance treatment vary to some extent between the country-specific national guidelines. Only IVIG for initial treatment of KD is consistently proposed throughout all guidelines, further therapeutic recommendations vary between the several national recommendations [ 3 ].…”
Section: Discussionmentioning
confidence: 99%